2010
DOI: 10.2106/jbjs.i.00969
|View full text |Cite
|
Sign up to set email alerts
|

The Offset of the Tibial Shaft from the Tibial Plateau in Chinese People

Abstract: The use of an anterolaterally offset tibial keel or stem seems more suitable for Chinese patients undergoing primary or revision total knee arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 14 publications
2
41
0
Order By: Relevance
“…However, Asian people generally have a varus knee alignment [8,20] and Asian patients with varus knee osteoarthritis (OA) have varying degrees of tibia vara [12,16,24]. This anatomic variance has made it difficult to achieve proper frontal alignment and proper component positioning in TKA because the TSA does not align with the TMA and passes through a point lateral to the center of the tibial eminence [12,14,20,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Asian people generally have a varus knee alignment [8,20] and Asian patients with varus knee osteoarthritis (OA) have varying degrees of tibia vara [12,16,24]. This anatomic variance has made it difficult to achieve proper frontal alignment and proper component positioning in TKA because the TSA does not align with the TMA and passes through a point lateral to the center of the tibial eminence [12,14,20,24].…”
Section: Introductionmentioning
confidence: 99%
“…This anatomic variance has made it difficult to achieve proper frontal alignment and proper component positioning in TKA because the TSA does not align with the TMA and passes through a point lateral to the center of the tibial eminence [12,14,20,24]. Consequently, lateralization of the tibial component is required to accord its center with the TSA, and it often needs downsizing of the component to avoid lateral overhang by the prosthesis.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, more than 50,000 patients underwent TKA in 2008, and this number will likely increase as the population ages. However, almost all prosthetic implants have been designed and manufactured to accommodate the knee anatomy of Western Caucasians, and there is some doubt about the application of these systems to Asians, as the femoral size of Asians differs from that of Caucasians [1-8]. Moreover, even if the smallest size from each Western prosthesis company is used, it may be too big for some Asian subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Hicks et al observed a variability in the location of the tibial canal of 1-15 mm from any direction to the center of the tibial component [16]. Because of the variations in anatomy, the use of a straight stem is not always possible and can lead to a poor coverage of the proximal part of the tibia and overhang of the tibial tray, coronal or sagittal malalignment of the mechanical axis of the knee, and non-filling of the tibial canal [18][19][20]. Therefore, in order to achieve maximal coverage of the tibial plateau without overhang and a well-centered stem, a tibial component with an offset stem is often needed.…”
Section: Anatomical Mismatchmentioning
confidence: 99%